Immunogenicity of constitutively active V599EBRaf - Andersen, Mads Hald; Ugurel, Selma; Schadendorf, Dirk (Cancer research, 2004)
Activating BRAF somatic missense mutations within the kinase domain are present in 60-66% of melanomas. The vast majority of these represent a single substitution of glutamate for valine (V599E). Here, we demonstrate spontaneous HLA-B*2705-restricted cytotoxic T-cell responses against an epitope derived from V599EBRaf. These T-cell responses were mutation specific as the corresponding epitope derived from wild-type BRaf was not recognized. The loss of the V599EBRAF genotype during progression from primary to metastatic melanoma in patients with V599EBRaf specific T-cell responses suggests an active immune selection of nonmutated melanoma clones by the tumor-bearing host.
Gesehen am 10.12.2020
Im Titel ist der Ausdruck "V599E" hochgestellt